2015
DOI: 10.1186/s13048-015-0180-0
|View full text |Cite
|
Sign up to set email alerts
|

Leptin, its receptor and aromatase expression in deep infiltrating endometriosis

Abstract: BackgroundThe aim of this study was to evaluate the leptin levels in the serum and peritoneal fluid (PF) and the protein expression in three different peritoneal ectopic implants in patients who underwent surgery for deep infiltrating endometriosis.MethodsAll patients had been treated at the Department of Gynecology of the Pedro Ernesto University Hospital, Rio de Janeiro. The study group consisted of 15 patients who underwent surgery for adnexal masses and infertility, while the control group consisted of ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“… 63 When a sizeable portion of tissue samples came from DE lesions, the evidence for aromatase positivity could easily evaporate. 64 , 65 , 66 , 67 This is because as lesions become more fibrotic and thus more rigid, the PGE 2 signaling would be attenuated, effectively cutting off this putative induction pathway.…”
Section: Discussionmentioning
confidence: 99%
“… 63 When a sizeable portion of tissue samples came from DE lesions, the evidence for aromatase positivity could easily evaporate. 64 , 65 , 66 , 67 This is because as lesions become more fibrotic and thus more rigid, the PGE 2 signaling would be attenuated, effectively cutting off this putative induction pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In a case-control study of 44 women with endometriosis and 42 healthy controls, Choi et al showed that leptin had an expression rate of 100% in ovarian endometrioma tissue specimens versus 59.5% in normal endometrium ( p < 0.001), independent of BMI or stage of disease [ 61 ]. Furthermore, Gonçalves et al found that leptin concentration in peritoneal fluid did not differ between patients and control ( p 0.18), and there was only borderline difference between those with ovarian implants and without them ( p 0.048) [ 57 ]. On the contrary, serum leptin levels were significantly higher both in patients versus controls ( p < 0.0001) and in those without ovarian implants versus those with implants ( p 0.04).…”
Section: Metabolic Surgery What It Is and How It Can Contribute To Endometriosis Researchmentioning
confidence: 99%
“…e action of leptin is roughly opposite to that of ghrelin, but its exact role depends on the energy state of the body: in steady body weight, it reflects the content of body fat; in cases of weight excess, its increased concentrations reduce appetite through central nervous signaling, whereas in conditions of food restriction, its levels decline in order to meet increased energy demands [44]. Apart from its metabolic properties, leptin is also known as a proinflammatory and angiogenetic mediator [55][56][57]. Increased levels of leptin have been identified in serum and peritoneal fluid specimens from women with endometriosis for more than two decades [55,58].…”
Section: Leptinmentioning
confidence: 99%
“…Aromatase protein level is increased in vaginal septum lesions and decreased in intestinal lesions in women with endometriosis (Goncalves et al 2015). Ovarian endometriomas express higher levels of aromatase and peroxisome proliferator-activated receptor gamma co-activator 1 alpha (PPARGC1A) than associated ectopic lesions and eutopic endometrium (Suganuma et al 2014).…”
Section: Pathogenesis and Progression Of Endometriosismentioning
confidence: 99%